The sequencing of the DNA chains in the light of the ethics of right-mindedness - Czerny, Janusz (Folia Philosophica, 2002)
The author of the present article undertakes the moral and ethical problem included in the question whether the sequencing of the DNA chains provides us with an absolutely reliable foundation upon which we may pass judgements on the identity of a human being. The views and opinions of scientists on this question are divided. The author undermines the absolutist thinking in this respect, and suggests the possibility for the “genetic reality” to admit mistakes.